# SOLUTION: Differentiate each function. Express your answer in a simplified factored form a) {{{ f(x)=(x+4)^3(x-3)^6 }}} b) {{{ y=(3x+5)/((1-(x^2))) }}} h) {{{ y=((x^2-3)/(x^2+3))^4 }}}

Algebra ->  Exponential-and-logarithmic-functions -> SOLUTION: Differentiate each function. Express your answer in a simplified factored form a) {{{ f(x)=(x+4)^3(x-3)^6 }}} b) {{{ y=(3x+5)/((1-(x^2))) }}} h) {{{ y=((x^2-3)/(x^2+3))^4 }}}       Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Mathway solves algebra homework problems with step-by-step help!

 Algebra: Exponent and logarithm as functions of power Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Exponential-and-logarithmic-functions Question 183798: Differentiate each function. Express your answer in a simplified factored form a) b) h) Answer by stanbon(60771)   (Show Source): You can put this solution on YOUR website!Differentiate each function. Express your answer in a simplified factored form a) f(x)=(x+4)^3(x-3)^6 Use the product rule: f'(x) = (x+4)^3